2013
DOI: 10.1073/pnas.1306911110
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of a peptide–morpholino oligonucleotide conjugate and a cell-penetrating peptide as an antibiotic

Abstract: A cell-penetrating peptide (CPP)-morpholino oligonucleotide (MO) conjugate (PMO) that has an antibiotic effect in culture had some contaminating CPPs in earlier preparations. The mixed conjugate had gene-specific and gene-nonspecific effects. An improved purification procedure separates the PMO from the free CPP and MO. The gene-specific effects are a result of the PMO, and the nonspecific effects are a result of the unlinked, unreacted CPP. The PMO and the CPP can be mixed together, as has been shown previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 11 publications
(20 reference statements)
0
40
0
Order By: Relevance
“…For instance, a PMO targeting the highly conserved region of the E. coli gyrA was recently shown to effectively inactivate several species of Gram-positive and Gram-negative bacteria, when used in the micro-molar range [36].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a PMO targeting the highly conserved region of the E. coli gyrA was recently shown to effectively inactivate several species of Gram-positive and Gram-negative bacteria, when used in the micro-molar range [36].…”
Section: Discussionmentioning
confidence: 99%
“…Specific EGSs complementary to the selected sites were synthesized. The peptide YARVRRRGPRGYARVRRRGPRR was conjugated to a MO with the same sequence as the EGS to generate the PPMO (13).…”
Section: Methodsmentioning
confidence: 99%
“…The sequence of the MO thereby decides the fate of the endogenous transcript. For example, MOs with External Guide Sequence (EGS) conjugated to peptides (PPMOs) have been designed to target essential genes of several pathogenic bacteria and have displayed strong antibacterial activity (10)(11)(12)(13). Similarly, PPMOs targeting the P. falciparum PfGyrA and PfPAT RNAs for RNase P-mediated cleavage inhibit parasite growth in the low micromolar range (4,(14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Russell et al [31] recently reported the discovery of a superfamily of bacterial phospholipases that act as antibacterial effectors in inter-and intra-species interactions by degrading the major component of bacterial cell membranes, namely phosphatidylethanolamine. Of special interest from a synthetic biology perspective are developments at the interface of chemistry and biology, such as the establishment of a peptide-morpholino oligonucleotide conjugate which, in combination with a bacteriostatic cell-penetrating peptide, exerts antibiotic activity over a wide range of pathogen species [32].…”
Section: Classical Approaches To Antibiotic Biosynthesismentioning
confidence: 99%